Shared signaling pathways in Alzheimer's and metabolic disease may point to new treatment approaches. (10th September 2020) - Suresh, Jahnavi; Khor, Ing Wei; Kaur, Prameet; Heng, Hui Li; Torta, Federico; Dawe, Gavin S.; Tai, E Shyong; Tolwinski, Nicholas S.
Abstract : 'A peculiar severe disease process of the cerebral cortex' are the exact words used by A. Alzheimer in 1906 to describe a patient's increasingly severe condition of memory loss, changes in personality, and sleep disturbance. A century later, this 'peculiar' disease has become widely known as Alzheimer's disease (AD), the world's most common neurodegenerative disease, affecting more than 35 million people globally. At the same time, its pathology remains unclear and no successful treatment exists. Several theories for AD etiology have emerged throughout the past century. In this review, we focus on the metabolic mechanisms that are similar between AD and metabolic diseases, based on the results from genome‐wide association studies. We discuss signaling pathways involved in both types of disease and look into new optogenetic methods to study the in vivo mechanisms of AD. Abstract : This review focuses recent findings that relate metabolic disease to Alzheimer's disease especially considering the similarities between neurodegeneration and pancreatic degeneration due to protein aggregates. It proposes a new, optogenetic model for studying protein aggregation in vivo that has been tested in three model organisms.